2016
DOI: 10.1016/j.cattod.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CO, H2 and C3H6 on Cu-SSZ-13 catalyzed NH3-SCR

Abstract: We investigated the steady-state and transient effects of reductants (CO, H 2 and C 3 H 6 ) on NO 2 reduction, NH 3 -SCR (selective catalytic reduction), NH 3 adsorption and oxidation, and N 2 O production on a Cu-SSZ-13 monolithic catalyst. The three reductants affect to different extents the standard SCR (NO + NH 3 + O 2 ), fast SCR (NO + NH 3 + NO 2 ), and slow SCR (NH 3 + NO 2 ). This study underscores the importance of accounting for the impact of reducing agents on conventional NH 3 -SCR reaction mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…The superior catalytic conversion of propylene was accompanied by a higher selectivity toward s CO and CO2 formation, with a larger CO2 fraction at low temperatures (Figures 2a and S4). Analogously as observed for Fe-ZSM-5, the CO2 proportion decreased with increasing temperature from 55% at 300 °C to 41% at 500 °C, which is in line with previous studies [26]. Although the primary oxidation products are carbon oxides, the higher conversion also resulted in increased quantities of other emissions.…”
Section: Hydrocarbon Oxidation At Elevated Pressure In the Presence Of Oxygensupporting
confidence: 90%
“…The superior catalytic conversion of propylene was accompanied by a higher selectivity toward s CO and CO2 formation, with a larger CO2 fraction at low temperatures (Figures 2a and S4). Analogously as observed for Fe-ZSM-5, the CO2 proportion decreased with increasing temperature from 55% at 300 °C to 41% at 500 °C, which is in line with previous studies [26]. Although the primary oxidation products are carbon oxides, the higher conversion also resulted in increased quantities of other emissions.…”
Section: Hydrocarbon Oxidation At Elevated Pressure In the Presence Of Oxygensupporting
confidence: 90%
“…According to the results of a previous study, the prevalence of dental caries among Lisu children was estimated to be 51% [16]. With the estimated 7% width of the 95% confidence interval, approximately 400 children were required according to the sample size calculation formula ( n = 4 × 1.962 × p × [1-p]/L 2 ; [n: number of participants, p: prevalence of diseases, and L: width of 95% confidence interval]).…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological data for dental diseases can serve as a basis for planning and implementing services to enhance the oral health status of the Lisu children. Only one study, published in 2009, reported their dental caries status; however, that study did not follow the dental caries diagnostic criteria of the World Health Organization (WHO) and failed to study the impact of social determinants on children’s dental caries status [16]. The purpose of the present study was to study the dental caries status and its risk indicators among Lisu children aged 5 in Yunnan, China.…”
Section: Introductionmentioning
confidence: 99%
“…It is an attractive and promising denitrification technology. Therefore, it is urgent to study CO-SCR technology [187][188][189]. Besides, precious metals are expensive, have limited reserves and have poor high temperature performance.…”
Section: Co-scrmentioning
confidence: 99%